PENGEMBANGAN PEGAWAI PADA BIRO UMUM DAN KEUANGAN KANTOR PUSAT ADMINISTRASI UNIVERSITAS SYIAH KUALA BANDA ACEH - Cut Nursamadiati; Murniati AR; Bahrun . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
The objective of this research was to find out the employee planning, the development strategies, and the obstacles found by a number of division and sub-division heads in the employee development of Administrative Office of Syiah Kuala University, Banda Aceh. The data for this qualitative research were collected by doing interview, observation, and documentation. The analysis consists of three activities, namely data reduction, data display, and verification. The subjects of this research were the vice-rectors, the heads of divisions and sub-divisions, and the employees. The results of this research indicated that: (1) The employee planning was done by arranging several programs of development and empowerment and adjusting the educational background of an employee with his position; (2) The strategies of employee development consist of coaching dan giving the chances to the employees to be the participants of education and training programs organized by Syiah Kuala University or other related institutions and agencies; (3) The obstacles found by the heads of divisions and sub-divisions were the internal factors such as the internal aspects, namely the elderly, limited funding for the development of education and should use their own cost, and sometimes inconsistency in program implementationcaused by the priority scale. In addition, there are also problems of external whom the government rules that restrict employees to continue their education.Keywords: employee development, educational resource management.